Muscling in on new worlds : Jews, sport, and the making of the Americas - Rein, Raanan, 1960-; Sheinin, David. (Jewish Latin America, 2015)
Muscling in on New Worlds brings together a dynamic new collection of studies that approach sport as a window into Jewish identity formation in the Americas. Articles address football/soccer, yoga, boxing, and other sports as crucial points of Jewish interaction with other communities and as vehicles for reconciling the legacy of immigration and Jewish distinctiveness in new world national and regional contexts.